Thermal Performance Study of Composite Phase Change Material with Polyacrylicand Conformal Coating - Kee, S.Y.; Munusamy, Y.; Ong, K.S.; Metselaar, H.S.C.; Chee, S.Y.; Lai, K.C. (MDPI, 2017)
The composite PCM was prepared by blending polymethyl methacrylate (PMMA) and myristic acid (MA) in different weight percentages. The MA and PMMA were selected as PCM and supporting material, respectively. As liquid MA may leak out during the phase transition, this study proposes the use of two coatings, namely a polyacrylic coating and a conformal coating to overcome the leakage problem. Both coatings were studied in terms of the leakage test, chemical compatibility, thermal stability, morphology, and reliability. No leakage was found in the PCMs with coatings compared to those without under the same proportions of MA/PMMA, thus justifying the use of coatings in the present study. The chemically compatibility was confirmed by FTIR spectra: the functional groups of PCMs were in accordance with those of coatings. DSC showed that the coatings did not significantly change the melting and freezing temperatures, however, they improved the thermal stability of composite PCMs as seen in TGA analysis. Furthermore, the composite PCMs demonstrated good thermal reliability after 1000 times thermal cycling. The latent heat of melting reduced by only 0.16% and 1.02% for the PCMs coated with conformal coating and polyacrylic coating, respectively. Therefore, the proposed coatings can be considered in preparing fatty acid/PMMA blends attributed to the good stability, compatibility and leakage prevention.